NATO 2030 Towards a New Strategic Concept and Beyond (Brookings Institution Press, 2021)
The North Atlantic Treaty Organization (NATO) is the world's largest, most powerful military alliance. The Alliance has navigated and survived the Cold War, the collapse of the Soviet Union, and the post-9/11 era. Since the release of the 2010 Strategic Concept, NATO's strategic environment has again undergone significant change. The need to adapt is clear. An opportunity to assess the Alliance's achievements and future goals has now emerged with the Secretary General's drive to create a new Strategic Concept for the next decade-an initiative dubbed NATO 2030. A necessary step for formulating a new strategic outlook will thus be understanding the future that faces NATO. To remain relevant and adjust to new circumstances, the Alliance must identify its main challenges and opportunities in the next ten years and beyond.This book contributes to critical conversations on NATO's future vitality by examining the Alliance's most salient issues and by offering recommendations to ensure its effectiveness moving forward. Written by a diverse, multigenerational group of policymakers and academics from across Europe and the United States, this book provides new insights about NATO's changing threat landscape, its shifting internal dynamics, and the evolution of warfare. The volume's authors tackle a wide range of issues, including the challenges of Russia and China, democratic backsliding, burden sharing, the extension of warfare to space and cyberspace, partnerships, and public opinion. With rigorous assessments of NATO's challenges and opportunities, each chapter provides concrete recommendations for the Alliance to chart a path for the future. As such, this book is an indispensable resource for NATO's strategic planners and security and defense experts more broadly.